Preparation of a composite material based on self-assembly of biomass carbon dots and sodium alginate hydrogel and its green, efficient and visual adsorption performance for Pb2+. Issue 1 (February 2022) - Zhang, Siyi; Arkin, Kamile; Zheng, Yuxin; Ma, Jicheng; Bei, Yuyang; Liu, Di; Shang, Qingkun
Abstract: In this paper, an environmentally friendly, visible and easy-to-recycle spherical adsorbent (SA@PEI-CDs, SA: sodium alginate, PEI: polyethyleneimine, CDs: carbon dots) has been prepared from functionalized positively charged biomass carbons dots (PEI-CDs) and anionic polyelectrolyte sodium alginate (SA) through electrostatic self-assembly. SA@PEI-CDs can efficiently and preferentially adsorb Pb 2+ . Compared to bare SA, the adsorption capacity of SA@PEI-CDs increased from 206.93 mg/g to 380.39 mg/g (at pH=4), which enhanced 83.82%. It can still maintain 85.67% of the original adsorption capacity after five cycles. The quenching of the blue fluorescence of the adsorbent derived from carbon dots indicates that the adsorption process has reached saturation. The investigation about the adsorption isotherm models, kinetics and thermodynamic parameters reveals that the adsorption process follows Freundlich isotherm model based on chemical adsorption, which is an endothermic spontaneous reaction with an increase in entropy. The possible adsorption mechanism is electrostatic attraction, ion exchange, and together with the coordination of -NH2, -OH, -COOH with Pb 2+ . In addition, the extremely easy-to-recycle spherical adsorbent is also used in the multi-layer adsorption and separation of simulated sewage samples in the water purifier model. For simulated water samples whose concentration of five/three types of heavy metal ions exceeds 100 times the standard, after using adsorbent SA@PEI-CDs for two or three consecutive adsorptions, the content of heavy metals decreases rapidly, which is far below the limit value of high-quality water. The Pb 2+ ion concentration decreased from 1.0 mg/L to 0.002540 mg/L and 0.003611 mg/L, respectively. Graphical Abstract: ga1 Highlights: ● SA@PEI-CDs is derived from functional biomass CDs and sodium alginate hydrogel. ● SA@PEI-CDs can preferentially and selectively adsorb heavy metal Pb 2+ . ● The blue fluorescence of PEI-CDs can indicate the progress of adsorption. ● SA@PEI-CDs is easy to separate and will not cause secondary pollution. ● The process is chemical adsorption, assisted by intra-particle diffusion.